Genetic polymorphisms variants in interleukin-6 and interleukin- 1beta patients with obstructive sleep apnea syndrome in East Northern Turkey - Ilhami Gok; Nergiz Huseyinoglu; Dogan Ilhan (Medicinski glasnik, 2015)
Aim: To investigate the relationship of IL-1? and IL-6 cytokine gene polymorphisms with obstructive sleep apnea syndrome (OSAS) in 61 patients admitted to the neurology clinic in Kafkas University Hospital with insomnia problem who were diagnosed with OSAS in sleeping labs, and 80 healthy subjects not associated with the syndrome. Methods: Blood samples were taken to isolate DNA from patients diagnosed with OSAS based on polysomnography results and healthy controls. DNA amplification of the genes was performed with PCR. Amplification products were cut with the restriction enzymes in order to determine IL-1 gene (TaqI) and IL-6 gene (Lwel) polymorphisms. The cut DNA fragments were carried out in agarose gel electrophoresis, and RFLP analysis was performed by utilizing the images with gel imaging system. PCR products were sequenced with an Applied Biosystems Automated Sequencer. Results: Polymorphic changes were observed for IL-1? gene in 26 of 62 patients (41.9%), and 16 of the 80 (25.8%) in the control group. The incidence of polymorphic changes in IL-6 gene was in seen in seven (of the 62 patients) (11.3%), and in the 16 (20%) controls. Conclusion: The findings on the genomic level in OSAS may provide an important contribution to diagnosis of obstructive sleep apnea syndrome in clinical practice, as well as it helps to obtain the results easily about environmental and genetic interaction of OSAS patients.
Keywords: OSAS; cytokine genes; RFLP; Turkey